Maximum oxygen uptake utilising different treadmill protocols. Issue 2 (June 1984) - Davies, B.; Daggett, A.; Jakeman, P.; Mulhall, J.
Abstract : The study compared five treadmill protocols (four utilising a motorised, and one a non-motorised, treadmill) on maximum oxygen uptake. The five male and five female subjects, all actively engaged in training, were assigned the tests in random order. Statistical analysis revealed no significant differences between the five protocols for maximal oxygen uptake, maximum ventilation, maximum heart rate and blood lactate inflection point, relative to maximal oxygen uptake. Significant differences were observed between the 3' protocol with incline increments of 1.5% and all other protocols on time to exhaustion (p = less than 0.01) and maximum blood lactate levels (HLA, p = less than 0.05). The results indicate that the protocols used in this study did not significantly influence the maximum oxygen uptake attained.